2017
DOI: 10.3748/wjg.v23.i11.2037
|View full text |Cite
|
Sign up to set email alerts
|

Is endoscopic ultrasonography essential for endoscopic resection of small rectal neuroendocrine tumors?

Abstract: AIMTo evaluate the importance of endoscopic ultrasonography (EUS) for small (≤ 10 mm) rectal neuroendocrine tumor (NET) treatment.METHODSPatients in whom rectal NETs were diagnosed by endoscopic resection (ER) at the Pusan National University Yangsan Hospital between 2008 and 2014 were included in this study. A total of 120 small rectal NETs in 118 patients were included in this study. Histologic features and clinical outcomes were analyzed, and the findings of endoscopy, EUS and histology were compared.RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…EUS could accurately diagnose the depth of lesions as small as 2 mm in diameter [ 16 ]. These results were corroborated in a 2017 study by Park et al, which demonstrated that EUS-determined size correlated well with both endoscopic and histologic estimation [ 17 ]. EUS accuracy in determining depth of invasion was reported to be 92.5% [ 17 ].…”
Section: Diagnosissupporting
confidence: 60%
See 1 more Smart Citation
“…EUS could accurately diagnose the depth of lesions as small as 2 mm in diameter [ 16 ]. These results were corroborated in a 2017 study by Park et al, which demonstrated that EUS-determined size correlated well with both endoscopic and histologic estimation [ 17 ]. EUS accuracy in determining depth of invasion was reported to be 92.5% [ 17 ].…”
Section: Diagnosissupporting
confidence: 60%
“…These results were corroborated in a 2017 study by Park et al, which demonstrated that EUS-determined size correlated well with both endoscopic and histologic estimation [ 17 ]. EUS accuracy in determining depth of invasion was reported to be 92.5% [ 17 ]. Yet another study reported that pre-operative depth determination by EUS was 100% [ 18 ].…”
Section: Diagnosissupporting
confidence: 60%
“…After endoscopic resection it is essential to identify risk factors of metastatic disease (LNþ or Mþ) in order to identify high-risk tumours requiring a specific workup and surgical management with lymphadenectomy. Rectal EUS and MRI seem useful in this setting 11 even if a recent study reported that they do not accurately predict residual disease. 30 Size is an indisputable risk factor for metastatic progression, 4,16,17 but with disparities between studies: herein, 8/287 (3%) of r-NETs < 10 mm showed metastatic progression; Soga found a rate of 58/595 (10%), 17 while Park et al found no metastatic tumours among r-NET < 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…However, endoscopic resections have yet to prove their effectiveness (R0 resection) and safety; previous reports concerning the management of small r-NETs remain limited to several single-institution retrospective studies with a small number of cases, and large Asian studies where the epidemiology of r-NETs, endoscopic expertise and health services are different to those of Western countries. [4][5][6][7][8][9][10][11] We therefore conducted a large multicentre nationwide study in France to evaluate the outcomes of non-metastatic r-NETs 2 cm in size diagnosed endoscopically. The primary objective was to describe the proportion of R0 resection.…”
Section: Introductionmentioning
confidence: 99%
“…Rectal NENs in EUS typically present as hypoechoic, homogenous lesions derived from the submucosal layer. Some recent studies show low potential of malignancy and indolent behaviour of small rNENs [19][20][21][22], suggesting that EUS may not be essential before endoscopic treatment of rNENs < 10 mm in size [19,21]. This approach that shifts the indications for EUS (from 5 to 10 mm), taking into account earlier observations showing metastatic potential of well-differentiated and small rNENs, remains, in our opinion, controversial [23].…”
Section: Reviewmentioning
confidence: 90%